Love and memory: a Platonic strategy for identity and immortality (Circe de clásicos y modernos, 2021)
Here, I address the link between ἔρως-μνήμη as a strategy to attain identity and immortality in two platonic dialogues. In the Symposium I show that love and memory help to: i) a faithful survival of the ἑρωτικοὶ λόγοιin the narrative weaving; ii) an aliud pro alio preservation of identity and immortality through the procreation of individuals of the same species, enduring productions in the cultural field and the body-mind elements of each individual. In the Phaedrus I tackle the interconnection “love-reminiscence-personal identity-immortality” in order to distinguish: i) those who, being unable to recall the eidetic realm, reproduce their psychosomatic configuration at the present time and similar psychosomatic configurations in their next lives; ii) the philosophers for whom, thanks to their love for the beautiful, ἀνάμνησιςand a god-like immortality are available along with their sharing in the noetic activity of winged Eros.
Keywords: love; memory; identity; inmortality; Plato